ISLAMIC PRAYER IS EFFECTIVE TO REDUCE PAIN AND ANXIETY PATIENTS WITH ACUTE MYOCARDIAL INFARCTION IN ICVCU : A PILOT STUDY] - Arif Adi Setiawan; Shofa Chasani; Mardiyono Mardiyono (Jurnal LINK, 2016)
Peak periods of pain and anxiety begins in the first 12 hours of entry ICVCU (Intensive Cardiovascular Care Unit) and improve after 48 hours until the patient was transferred to the ward. The study was to evaluate the efftects of Islamic Prayer in reducing pain and anxiety in patients with AMI in ICVCU. The study was A quasi experimental pre and post test design. The Samples were AMI patients hospitalized for 3 days. Islamic Prayer is composed by reciting Qur’an, prayer, and zikr. Pain was measured by the Numeric Rating Scale for Pain and anxiety was measured by the Numerical Rating Scale for Anxiety (NRSA). The data pain and anxiety were analysized by paired t-test. The findings show that there were significant reductions in mean pain scores and anxious before and after intervention after entering ICVCU Islamic Prayer interventions effectively reduce pain at 12 hours (t = 6.293, p = .000), 24 hours (t = 5.191, p = .000) and 48 hours after admission (t = 6.698, p = .000) and anxious 12 hours (t = 6.293, p = .000), 24 hours (t = 5.506, p = .000), 48 hours (t = 5.234, p = .000). which means that Islamic Prayer is effective to reduce pain and anxiety in patients with AMI in ICVCU.